The student perceptions on online biology learning during the Covid-19 pandemic - Fitri Wahyuriyani; A. Wahab Jufri; Imam Bachtiar (Jurnal Pijar Mipa, 2023)
The COVID-19 pandemic has changed the patterns of learning in schools. This study aims to determine: (1) the pattern of implementation of online Biology learning at SMAN 1 Kediri; (2) students' perceptions of online Biology learning at SMAN 1 Kediri; (3) differences in students' perceptions of online Biology learning at SMAN 1 Kediri based on grade level; 4) differences in students' perceptions of online biology learning at SMAN 1 Kediri based on gender. This type of research is exploratory, descriptive research. The population in this study were students majoring in science at SMAN 1 Kediri. The research sample consisted of 137 students. The sampling technique used was stratified random sampling. Data analysis was carried out using qualitative and quantitative approaches (calculating categories, percentages, and median tests). The results show that the implementation of online Biology learning at SMAN 1 Kediri used WhatsApp Group (WAG) and Google Classroom (GC) media. Students' perceptions of online learning of Biology subjects during the Covid-19 pandemic varied, both positive and negative. Online learning provides flexibility and easy access to learning resources, but there are also difficulties in student-teacher interaction and understanding of the learning material. Students' perceptions of online learning are similar between grade levels and genders.